Introduction to Guattari on Trandisciplinarity. (September 2015) - Goffey, Andrew
Written roughly a year before the end of his life, Guattari's 'The Ethico-Political Foundations of Interdisciplinarity' elaborates an account of transdisciplinary research processes closely informed by his conception of transversality. Tacitly critiquing institutions of research that separate it from the political practices associated with the reinvention of democracy, the paper explores in particular the possibilities of conducting transversal research into urban life, and speculates on the value of information technology.